THE THEOLOGICAL DISCOURSE AND SLAVERY: MANUEL RIBEIRO ROCHA E AZEREDO COUTINHO - Gonçalves Guimarães, Jorge (2019)
Theologians and jurists stood up for slavery, making use of stronger or weaker attenuating reasons. Both Ribeiro da Rocha and Azeredo Coutinho’s points of view, which very often show a striking contrast, are a good example of this.